The Effect of Cumin on the Formation of β-Carboline Heterocyclic Amines in Smoked Meat and Simulated Systems - Xiuxiu Liu; Wenyu Chen; Minghao Sun; Xufang Lv; Xing Shen; Zhongping Chai; Maomao Zeng (Foods)
In this study, we aimed to investigate the inhibitory effects of cumin and cumin extracts from different origins (Hami, Turpan, and Hetian) on the formation of β-carboline heterocyclic amines (HCAs) in smoked meat and simulated systems, and to assess their potential as natural inhibitors in the food industry. The novelty of our research lies in the comprehensive comparative analysis of cumin extracts from different origins, which has not been fully explored in previous studies. We first conducted a quantitative analysis of the total phenol and flavonoid content in cumin extracts from the three origins and evaluated their antioxidant capacities. Subsequently, through simulation experiments, we assessed the inhibitory effects of these extracts on the formation of β-carboline heterocyclic amines and determined their free radical scavenging abilities. To further validate the practical application potential of these extracts, we prepared meat patty samples containing different concentrations of cumin powder, simulating actual processing conditions. The experimental results showed that while the total phenol content in cumin extracts from all origins was similar, averaging around 1.56 mg/g, there was a significant difference in the total flavonoid content, with the highest level observed in the Hetian cumin extract at 6.7 mg/g. Additionally, the Hetian cumin extract demonstrated superior antioxidant capacity, with an FRAP antioxidant activity reaching 21.04 μM TE/g dw, the highest among all samples. Our study also found that the inhibitory effect of cumin extracts on HCA formation was closely related to their free radical scavenging ability, with the Hetian cumin extract showing the strongest scavenging capacity. The addition of cumin powder to meat patties significantly reduced the content of β-carboline heterocyclic amines, particularly at lower cumin concentrations. In summary, our research results highlight the potential of cumin, especially from Hetian, as a natural inhibitor of β-carboline heterocyclic amine formation in processed meats. This study not only provides the food industry with a potential natural additive to improve food safety and quality, but also offers new directions for future research, namely by comparing natural plant extracts from different origins to explore their potential applications in food processing.